PENERAPAN MODEL PEMBELAJARAN PROJECT CITIZEN UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PRESTASI BELAJAR - Hera Astuti; Bambang Sahono (UNIB Press, 2022)
This study aims to describe the application of the project citizen learning model the effectiveness of the project citizen learning model to improve critical thinking skills and learning achievement in Civics class XI SMA Negeri 1 Kikim Timur subjects. The research method used was Classroom Action Research (CAR) and quasi-experimental. The subjects of this study were class XI students of SMA Negeri 1 Kikim Timur in the second semester of the 2020/2021 academic year. The number of students for the PTK class was 30 people, for the experimental class there were 30 people, and for the control class there were 30 people. Methods of data collection in this study using the observation sheet project citizen learning model, the observation sheet for critical thinking skills and test learning outcomes. The data analysis used the average score and tests which consisted of a different test between cycles and an unrelated two-sample difference test. The results showed that the application of the project citizen learning model can improve critical thinking skills, learning achievement and effectively improve student learning outcomes in Civics class XI SMA Negeri 1 Kikim Timur.